Assessing the drivers and impact of international marketing agility. Issue 2 (8th April 2019) - Asseraf, Yoel; Lages, Luis Filipe; Shoham, Aviv
Abstract : Purpose: The purpose of this paper is to develop and empirically test a new conceptualization of international marketing agility (IMA). Importantly, the empirical test includes agility's drivers, outcomes and boundary conditions for its impact on international market performance. Design/methodology/approach: The authors draw on the resource-based view and dynamic capabilities theories to develop a model and test it quantitatively via structural equation modeling with survey data from 195 Israeli exporters. In addition, the authors seek insights into the findings through post hoc in-depth interviews. Findings: The results indicate that IMA enhances international market performance directly as well as indirectly through exporter's new products advantage. Interestingly, while promotion adaptation strengthens the positive effect of IMA on new products advantage, product adaptation does not. Research limitations/implications: Managers need to develop and improve marketing planning and flexibility maintenance capabilities. Furthermore, while maintaining an emphasis on marketing planning, they need to guard against inertia by embracing outside views, a wider range of solutions and a greater awareness of others' decision-making styles to develop flexibility maintenance capability and achieve superior IMA. Originality/value: A new conceptualization and operationalization of agility specific to an international marketing context is tested empirically. The complementary role of marketing planning capability and flexibility maintenance capability is demonstrated. Importantly, the vital role of new products advantage as a mediator between agility and performance is examined and the moderating role of international marketing strategy adaptation is investigated.